956 Patient-Reported Outcomes After Platelet Rich Plasma Injections for Elbow Tendinopathies. (19th August 2022) - Haruna, M; Stevens, R; Macinnes, S
Abstract: Introduction: Elbow tendinopathies affect 1–3% of the population, with 35–50 years old most commonly being affected. It is work-related as such can lead to significant morbidity, time off work, and affect the income of patients as well as daily activities. Non-operative management is the recommended first step however, success is influenced by patient compliance. Autologous platelet-rich plasma injections are a novel approach to managing tendinopathies however, evidence of efficacy was determined by NICE to be inadequate as such recommended more research into its use. Aim: Assess patient-reported outcomes after PRP injections for management of elbow tendinopathies. Method: Retrospective study of 28 patients with chronic elbow tendinopathies treated with PRP injections between 2018–2020. Pre-and Post-procedure outcomes were measured using the Oxford Elbow Score questionnaire. Average f/u duration-234 days. Results: 27 patients answered the questionnaire out of 28 total patients that underwent the procedure. Of the 27 patients, 20 patients (74%) reported improvement in symptoms and were satisfied with their outcomes after one injection. Conclusions: This study shows PRP injections are reasonable and efficient management for elbow tendinopathies in patients not managed medically. This helps strengthen arguments for PRP injections over steroids for tendinopathies as studies have shown that steroids have potential side effects, usually requires more than 1 injection for symptomatic relief and despite being beneficial in short term, is worse than other treatment options in the intermediate and long term for patients with tendinopathies. Our numbers also coincide with previous larger studies that showed ∼70% of patients reported symptoms improving after 1 injection.